Inflammatory Markers of ARDS Events among Patients with Severe and Critical COVID-19 Infection at Adam Malik General Hospital, Medan, North Sumatera - Eva Susanti Debora Hutabarat; Fajrinur Syarani; Syamsul Bihar; Putri Chairani Eyanoer (Respiratory Science, 2023)
Background: COVID-19 can cause fatal outcomes, especially acute respiratory distress syndrome (ARDS). It manifests as organ dysfunction during COVID-19's hyperinflammatory phase, which is associated with a high mortality rate. Data on the clinical characteristics and inflammation markers of patients with severe and critical degrees of COVID-19 with ARDS events are limited. Method: This study is carried out at the Haji Adam Malik General Hospital in Medan. We grouped 204 medical records from February to July 2022 of hospitalized patients with severe and critical COVID-19 cases into two groups, ARDS and non-ARDS. Characteristics of demographic and laboratory inflammatory markers upon admission between each group were collected. After collecting data and serving as categorical data in the frequency distribution table by SPSS ver 25.0. Results: We identified 116 patients (56.9%) who had ARDS event upon hospital admission. ARDS event are most commonly found in the elderly group and the median age of ARDS group patients was 59.5 years higher than the non-ARDS group. Male patients were more likely to have ARDS than female patients. Compared with the non-ARDS group, ARDS group patients had lymphocytopenia, neutrophilia, increased neutrophil-to-lymphocyte ratio (NLR), Procalcitonin and C-Reactive Protein levels. Conclusion: Lymphocytopenia, neutrophilia, increased NLR, procalcitonin and CRP levels upon admission revealed that they were higher in ARDS patients compared to non-ARDS patients. It is critical to identify high-risk groups, such as male sex, the elderly, those with comorbidities, and patients with impaired inflammatory markers to prevent severe complications from COVID-19.